(3GdBOGH GdfGaYI HGdCdaGX GdoeNJGQI GdLGeYIs - (3LYaQ Hf eMeO GHf eNJGQ GdCaVdj, CHh GdaVd, GdedbH eLO Gdoedc , GHf nTreS GdpNndGaI,J (B622 (3g` s
(3ChdgG (B:s
"(3jDJj GdMceI ef jTGA, hef jDJ GdMceI abO ChJj NjQkG cKjQkG(B"(3, bGd QShd Gddg Udi Gddg Ydjg hSde(B: " (3GdMceI JRjO GdTQja TQaG (B" s
(3BNQgG (B:s
(3GdHOjY GdHGbj GdhGQK GdQTjO GdUHhQ GdPj djS ceKdg TF hgh GdSejY GdHUjQ fYe Gdehdi hfYe GdfUjQ s
(3HBNQgG JedjcGJ HYVgG eDQN SfI (B941(3g`s
(3bWYI ef fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B128 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B149s
Keywords: (3GdCOHs